The prognostic value of thromboelastography MA/R ratio in predicting mortality in acute respiratory failure patients - Zhang-Sheng Zhao; Zhen-Zhen Wang; Lei Wang; Li-Hui Qian; Bin Hu; You-Li Ma (PLoS ONE, 2026)
Thromboelastography (TEG) MA/R ratio reflects coagulation status and thrombus strength. This study evaluated its prognostic value in acute respiratory failure (ARF). A retrospective analysis of 371 ARF patients admitted to the ICU, stratified by MA/R quartiles. Outcomes included 28-day mortality, deep vein thrombosis (DVT), mechanical ventilation duration, and ICU stay. Cox proportional hazards regression model was used to assess hazard ratios, restricted cubic spline was employed to evaluate the nonlinear relationship between MA/R and mortality, and Kaplan-Meier analysis was conducted to compare survival time across different MA/R groups. Patients in the lowest MA/R quartile (Q1) had significantly higher 28-day mortality (59.8% vs. 22.1–28.0% in Q2-Q4; P < 0.001) and elevated inflammatory markers (cytokines, procalcitonin, lactate, creatinine; P < 0.05). DVT incidence, ventilation duration, and ICU stay did not differ between groups. Multivariate analysis identified MA/R as an independent mortality predictor ( P < 0.05), with mortality risk sharply increasing below a threshold of 9.7. Kaplan-Meier curves showed shorter survival in Q1 ( P < 0.001). The MA/R ratio measured at ICU admission can rapidly identify coagulation dysfunction in patients with acute respiratory failure, with a low MA/R ratio being a strong indicator of poor prognosis.